PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN CHATIME DI KOTA DEPOK - Dewisartika, Andryani; Nurhayaty, Ety (LP2M Universitas Bina Bangsa, 2024)
In the current era of globalization, the beverage industry sector is experiencing rapid and significant growth in various regions including Depok City. Currently, one of the most popular and growing beverages in Depok City is bubble tea. Chatime is known as a pioneer in the bubble tea business. Chatime was founded in Taiwan in 2003. Chatime entered Indonesia in 2011 under the auspices of the Kawan Lama Group. The purpose of this study was to determine the effect of price and promotion on chatime purchasing decisions in Depok City. The method of analysis in this study uses a quantitative approach based on statistical data. The analysis method in this study uses several tests, namely starting from the validity test, reliability test, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression, t test, f test, and coefficient of determination test. The sampling method in this study was purposive sampling technique. The results of this study indicate that based on the t test, price and promotion have a positive and significant effect on purchasing decisions. Based on the results of the f test, Price and Promotion simultaneously have a positive and significant effect on Chatime Purchasing Decisions in Depok City. Based on the results of the simultaneous determination coefficient test, price and promotion have an influence of 70.5% on chatime purchasing decisions in Depok City, while the remaining 29.5% is influenced by other variables